Multisensory in-car warning signals for collision avoidance. - Ho, C; Reed, N; Spence, C (2007)
OBJECTIVE: A driving simulator study was conducted in order to assess the relative utility of unimodal auditory, unimodal vibrotactile, and combined audiotactile (i.e., multisensory) in-car warning signals to alert and inform drivers of likely front-to-rear-end collision events in a situation modeled on real-world driving. BACKGROUND: The implementation of nonvisual in-car warning signals may have important safety implications in lessening any visual overload during driving. Multisensory integration can provide synergistic facilitation effects. METHOD: The participants drove along a rural road in a car-following scenario in either the presence or absence of a radio program in the background. The brake light signals of the lead vehicle were also unpredictably either enabled or disabled on a trial-by-trial basis. RESULTS: The results showed that the participants initiated their braking responses significantly more rapidly following the presentation of audiotactile warning signals than following the presentation of either unimodal auditory or unimodal vibrotactile warning signals. CONCLUSION: Multisensory warning signals offer a particularly effective means of capturing driver attention in demanding situations such as driving. APPLICATION: The potential value of such multisensory in-car warning signals is explained with reference to recent cognitive neuroscience research.